H3K4me2 marks the enhancer: Enhancer logic in the zebrafish embryo. - Noura Maziak; Juan M Vaquerizas (PLoS Biology, 2025)
At a key point in development, the embryo activates its genome: a shift that is largely coordinated by maternally derived factors. A new study in PLOS Biology identifies H3K4me2-marked enhancers in zebrafish that function independently and mirror the gamete state.